2019
DOI: 10.1371/journal.ppat.1007871
|View full text |Cite
|
Sign up to set email alerts
|

The lectin-specific activity of Toxoplasma gondii microneme proteins 1 and 4 binds Toll-like receptor 2 and 4 N-glycans to regulate innate immune priming

Abstract: Infection of host cells by Toxoplasma gondii is an active process, which is regulated by secretion of microneme (MICs) and rhoptry proteins (ROPs and RONs) from specialized organelles in the apical pole of the parasite. MIC1, MIC4 and MIC6 assemble into an adhesin complex secreted on the parasite surface that functions to promote infection competency. MIC1 and MIC4 are known to bind terminal sialic acid residues and galactose residues, respectively and to induce IL-12 production from spl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 60 publications
2
36
0
11
Order By: Relevance
“…The lectins’ interactions with macrophages and dendritic cells are established by the recognition of TLR2 and TLR4 N-glycans and result in modulation of the immune response toward the Th1 axis. Sardinha-Silva et al ( 23 ) have recently demonstrated the importance of these lectins for the induction of early IL-12 production in T. gondii infection. Concerning the discrimination of which TLR2 N-glycans are targeted by Tg MIC1 and Tg MIC4, those occupying positions 2, 3, and 4, impact the Tg MIC1–TLR2 interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lectins’ interactions with macrophages and dendritic cells are established by the recognition of TLR2 and TLR4 N-glycans and result in modulation of the immune response toward the Th1 axis. Sardinha-Silva et al ( 23 ) have recently demonstrated the importance of these lectins for the induction of early IL-12 production in T. gondii infection. Concerning the discrimination of which TLR2 N-glycans are targeted by Tg MIC1 and Tg MIC4, those occupying positions 2, 3, and 4, impact the Tg MIC1–TLR2 interaction.…”
mentioning
confidence: 99%
“…Concerning the discrimination of which TLR2 N-glycans are targeted by Tg MIC1 and Tg MIC4, those occupying positions 2, 3, and 4, impact the Tg MIC1–TLR2 interaction. On the other hand, Tg MIC4 requires the TLR2 N-glycans linked to the sites 3 and 4 to interact with the receptor ( 23 ).…”
mentioning
confidence: 99%
“…MIC1 possui massa molecular de 49 kDa, é solúvel e multifuncional, capaz de se ligar a glicoconjugados que apresentam α2-3 sialilactosaminas na região terminal das Nglicanas (Blumenschein et al, 2007;Friedrich et al, 2010;Sardinha-Silva et al, 2017).…”
Section: As Proteínas De Micronema E a A Tividade Lectínica Do Compleunclassified
“…8B). Após o processo de diálise, realizou-se dois ensaios de controle de qualidade das lectinas recombinantes: o primeiro para averiguar a ligação das lectinas ao açúcar específico e outro para verificar a capacidade das lectinas estimularem macrófagos a produzirem IL-12 (Pinzan et al, 2015;Sardinha-Silva et al, 2017).…”
Section: A Produção Das Proteínas Recombinantes Mic1 E Mic4unclassified
“…A invasão da célula é um processo ativo. O parasito invade a célula hospedeira através da expressão e liberação de proteínas de micronemas (TgMICs) e de roptrias (ROPs e ROMs), organelas especializadas presentes na parte apical do parasito (SARDINHA-SILVA et al, 2017). As micronemas são responsáveis pela adesão do parasito à célula hospedeira (SOLDATI-FAVRE, 2008;SOUZA et al, 2010;JIMENEZ-RUIZ et al, 2016), enquanto as roptrias e grânulos densos estão envolvidos na invasão propriamente dita e formação do vacúolo parasitóforo, que é derivado da membrana celular do hospedeiro (SOUZA et al, 2010).…”
unclassified